Aedes breeding indices at public neglected areas: A case study in Batu Rakit Terengganu / Mahyudin Awang - Awang, Mahyudin (2014)
Introduction: This study focus the Aedes breeding in 'neglected area' at Tapak Pasar Malam, and Beach, Kg. Pengkalan Maras, Batu Rakit. Objectives: The indices associates to the knowledge, attitude and practice (KAP) level of the community members around the site. Besides this study is to identify the Aedes breeding places and the factor attract it such as type of container, pH, temperature and water conductivity. Methods: The mosquitos breeding container will be map point locations into Garmin GPS, and the characteristic is recorded. 60 respondent will be inteview. Results: Aedes breeding found in a wide range of pH, temperature and water conductivity. It is mean Aedes easily survives and breeding. Interpretation and conclusion: The respondent knowledge towards dengue is good. Unfortunately, 90% respondent believes the littering could be practise if trash bin not accommodate. Observation found majority of hawkers and visitors to the night market littering their waste same with visitors to the Beach, Kg. Pengkalan Maras. Law enforcement is necessary to prevent the habit of the community as well as the comprehensive implementation of Solid Waste and Public Cleansing (Act 672).